Quality Assurance & Regulatory Affairs for the Biosciences - O'Grady, Jack (Open textbook library., 2019)
This 125-page course textbook, entitled Quality Assurance & Regulatory Affairs for the Biosciences, was created by Jack O'Grady, M.S., professor at Austin Community College. This textbook accompanies the course BITC 1340: Quality Assurance for the Biosciences.